THE USE OF SMARTPHONE APPLICATIONS IN LEARNING ENGLISH VOCABULARY OF FIRST-YEAR STUDENTS AT VNU INTERNATIONAL SCHOOL - To Hoa, Nguyen Thi (VNU Journal of Foreign Studies; Vol 38 No 3DO - 10.25073/2525-2445/vnufs.4851, 2022)
This research focuses on the use of smartphone applications in learning English vocabulary of over 400 first-year students of elementary level at International School - Vietnam National University, Hanoi (VNU-IS). It helps to clarify what aspects students should know when learning a new word and aims to find out what criteria these students take into consideration when choosing smartphone applications to learn English vocabulary, which smartphone applications are most frequently used by them and how they evaluate the effectiveness of these smartphone applications in learning English vocabulary. From the data collected and the findings, some conclusions are made relating to the use of smartphone applications in English vocabulary learning of first-year elementary students at VNU-IS.